2011
DOI: 10.1007/s10464-011-9454-x
|View full text |Cite
|
Sign up to set email alerts
|

The ABLe Change Framework: A Conceptual and Methodological Tool for Promoting Systems Change

Abstract: This paper presents a new approach to the design and implementation of community change efforts like a System of Care. Called the ABLe Change Framework, the model provides simultaneous attention to the content and process of the work, ensuring effective implementation and the pursuit of systems change. Three key strategies are employed in this model to ensure the integration of content and process efforts and effective mobilization of broad scale systems change: Systemic Action Learning Teams, Simple Rules, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 34 publications
2
68
0
Order By: Relevance
“…In our view, this scepticism is consistent with a number of recent publications in this space. Despite the growing number of opinion pieces on the value of systems thinking for health 10,21 , and increased reporting of the use of both qualitative and quantitative systems techniques for health policy and prevention initiatives 22,23 , there needs to be greater engagement in the public health field with the full range of systems methodologies. 24 Based on the research findings presented here, a number of recommendations for future research, policy and practice are worth considering.…”
Section: Discussionmentioning
confidence: 99%
“…In our view, this scepticism is consistent with a number of recent publications in this space. Despite the growing number of opinion pieces on the value of systems thinking for health 10,21 , and increased reporting of the use of both qualitative and quantitative systems techniques for health policy and prevention initiatives 22,23 , there needs to be greater engagement in the public health field with the full range of systems methodologies. 24 Based on the research findings presented here, a number of recommendations for future research, policy and practice are worth considering.…”
Section: Discussionmentioning
confidence: 99%
“…Through this mobilization of effort, which might include joint training of staff from different organizations, creation of a family organization, enlisting businesses and other groups to provide tangible support for families, or other community-building strategies, segments of the community can come together. When communities become organized and pull together to accomplish a task, there are likely benefits to youth in the community, regardless of the focus of the task (Flaspohler et al 2011). Consistent with this would be the findings of Bickman et al (1999), who found that youth who did not receive formal services within a SOC improved in symptoms and mental health functioning at the same rate as (or, in some instances, a greater rate than) those who received comprehensive SOC services.…”
mentioning
confidence: 80%
“…This requires having strong organizations that provide the necessary services, as well as alignment and coordination among those organizations. This, in turn, requires policies, connections, and norms that promote effectiveness, responsiveness, collaboration, learning, and adaptation (Foster-Fishman & Watson, 2012). Foundations are increasingly seeking to improve the functioning of existing systems and to foster new systems that address unmet needs.…”
Section: Sectormentioning
confidence: 99%